Weakly Relative Poverty - Ravallion, Martin; Chen, Shaohua (MIT Press, 2015)
Prevailing measures of relative poverty are unchanged when all incomes grow or contract by the same proportion. This property stems from seemingly implausible assumptions about the disutility of relative deprivation and the cost of social inclusion. We propose ‘‘weakly relative’’ lines that relax these assumptions. On calibrating our measures to national poverty lines and survey data, we find that half the population of the developing world in 2005 lived in poverty, only half of whom were absolutely poor. The total number of poor rose over 1981 to 2005 despite falling numbers of absolutely poor. With sustained economic growth, the incidence of relative poverty became less responsive to further growth. The number of relatively poor rose, just as the numbers of absolutely poor fell.